2019
DOI: 10.2807/1560-7917.es.2019.24.42.1900592
|View full text |Cite
|
Sign up to set email alerts
|

The ‘Finnish new variant of Chlamydia trachomatis’ escaping detection in the Aptima Combo 2 assay is widespread across Norway, June to August 2019

Abstract: The ‘Finnish new variant of Chlamydia trachomatis’ (FI-nvCT), escaping detection in the Aptima Combo 2 assay (AC2), is widespread across Norway. From June to August 2019, 84% (81/97) of available AC2/Aptima CT discordant samples from five laboratories were confirmed as FI-nvCT. Two additional CT variants (CT 23S rRNA C1514T and G1523A) also escaped AC2 detection. The high FI-nvCT proportion might indicate a long-term national spread and it cannot be excluded that FI-nvCT emerged in Norway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 10 publications
(32 reference statements)
4
21
0
Order By: Relevance
“…However, some of these assays use only one target region for detection. Lessons from the Swedish nvCT (Ripa and Nilsson, 2006; Moller et al ., 2010; Unemo et al ., 2010; Unemo and Clarke, 2011) and the nvCT discovered in 2019 (Hokynar et al ., 2019; Johansen et al ., 2019; Rantakokko‐Jalava et al ., 2019; Roberts et al ., 2019; Unemo et al ., 2019a,b; Hadad et al ., 2020) have suggested that false‐negative results were generated due to genetic diversity in diagnostic methods using a single target. These findings suggest that the detection of more than one gene from C. trachomatis may be necessary to avoid false‐negative results due to mutation within the target sequences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some of these assays use only one target region for detection. Lessons from the Swedish nvCT (Ripa and Nilsson, 2006; Moller et al ., 2010; Unemo et al ., 2010; Unemo and Clarke, 2011) and the nvCT discovered in 2019 (Hokynar et al ., 2019; Johansen et al ., 2019; Rantakokko‐Jalava et al ., 2019; Roberts et al ., 2019; Unemo et al ., 2019a,b; Hadad et al ., 2020) have suggested that false‐negative results were generated due to genetic diversity in diagnostic methods using a single target. These findings suggest that the detection of more than one gene from C. trachomatis may be necessary to avoid false‐negative results due to mutation within the target sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, this mutation was located in the region originally utilized by the NAATs Aptima Combo 2 (AC2) (Hologic Inc., San Diego, CA, USA) to detect C. trachomatis , which were used in many countries worldwide. This new variant of C. trachomatis (nvCT) escaping detection in the AC2 assay has subsequently been detected in other European countries such as Sweden, England, Norway and Denmark (Johansen et al ., 2019; Roberts et al ., 2019; Unemo et al ., 2019b; Hadad et al ., 2020). Two additional C. trachomatis variants harbouring C1514T and G1523A mutations in the 23S rRNA target region, also escaped AC2 detection in England, Norway and Denmark (Johansen et al ., 2019; Roberts et al ., 2019; Hadad et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AC2 negative/equivocal-ACT positive) signalled the presence of the new strain. Data collected in subsequent investigations suggested a recent emergence of FI-nvCT in south-western Finland, Norway and Sweden with relatively low prevalence (ca 1-6%) among patients with C. trachomatis infections [1,[3][4][5]. We have developed and validated a research-use only Aptima-format surveillance NAAT designed specifically to detect the FI-nvCT strain.…”
mentioning
confidence: 99%
“…Our rapid communications on ongoing or emerging threats were published within 2 to 3 weeks of submission, creating awareness and providing evidence to support rapid public health action. Some examples of the rapids we published included the worsening epidemiological situation of carbapenemase-producing Enterobacteriaceae in Europe [13], a case of extensively drug-resistant typhoid fever imported from Pakistan to Denmark [14] and the detection of a Chlamydia trachomatis variant escaping detection by a widely used assay in Finland that was found in other European countries thereafter [15][16][17].…”
mentioning
confidence: 99%